Penggunaan Hasil Tindak Pidana untuk Sumbangan Dana Pemilu - Arifin, Ibrahim (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2024)
The utilization of proceeds from criminal activities for political campaign purposes in the context of General Elections, as donations from external sources, is feasible under money laundering practices. Relevant criminal provisions addressing this issue include Article 339, paragraph (1) of letter c of the Election Law, Article 5, paragraph (1) of the Money Laundering Law, and Article 137 of the Narcotics Law. Given that these provisions are lex specialis, it is essential to elucidate the parameters that will guide law enforcement officials in addressing the use of criminal proceeds for political campaigns and other electoral contests. This research employs normative juridical legal methods, focusing on an inventory of positive law. The findings indicate that the lex specialis derogat legi generali principle applies in implementing Article 339 paragraph (1) letter c of the Election Law, particularly concerning campaign participants receiving campaign fund donations from criminal activities. Article 5, paragraph (1) of the Money Laundering Law pertains to individuals who receive money or assets from criminal activities without the election participants' status. Election participants who accept the proceeds of crime for campaign funds may be suspected of being active perpetrators of money laundering or as parties who commit or facilitate money laundering.